Diverse Perceptions of Cross-Racial Adoption in South Africa. (March 2017) - Tanga, Pius T.; Nyasha, Kausi
Purpose: This study explored the perceptions of stakeholders regarding the practice of cross-racial adoption (CRA) in East London, South Africa. Method: A qualitative research design was used. Data were collected through individual interviews and focus group discussions from 23 participants. The data were analyzed qualitatively, using thematic analysis. Results: The results show that there are mixed perceptions among the participants, with White participants more likely than participants of other racial groups to support the practice of the CRA. The findings also revealed that the practice of CRA is a controversial, yet an increasing phenomenon in which most Black children are being adopted by White parents. Conclusion: It is concluded that although the practice of CRA is an acceptable form of custody of children in need of care and protection, it is still an area that requires more attention from scholars and researchers. Pertinent recommendations have been made to various stakeholders.